A HANDFUL OF REMARKS ON THE NECESSITY FOR COMMUNICATION OPTIMIZATION BETWEEN SWORN TRANSLATORS AND LAW ENFORCEMENT BODIES, FOR THE DEVELOPMENT OF STRATEGIES FOR ITS ACHIEVEMENT AND POTENTIAL BENEFITS - ZIELIŃSKI, Lech (Comparative Legilinguistics, 2016)
The author has been regularly cooperating with law enforcement bodies in the field of sworn translation and interpreting. The article is a thorough analysis of two extensive translation commissions, during the performance of which an attempt was made at the optimization of the translation process to save the translator’s time and public funds. The author assumes that completion of extensive translation services delivered for the Public Prosecutor’s Office is not always optimal. The author gives reasons for this situation and offers potential solutions aimed at the improvement and optimization of the work on more extensive translations. Due to the fact that both these cases differ in terms of efficiency of actions aimed at the optimization of the process, analytical criteria slightly differ, yet conclusions drawn are complementary. In the first case, an obstacle for effective communication between the translator and law enforcement bodies is the intermediary role of district prosecutor’s offices while applying for legal assistance, which substantially restricts the possibility of the translator contacting the person for whom translation is provided. The source of problems in the second case can be found in provisions of the Act of 25 November 2004 on the Profession of Sworn Translator, and specifically in Article 13. Conclusions are of a more practical nature, and their implementation can contribute to the improvement of communication between sworn translators and law enforcement bodies, to more effective spending of public funds and accelerating proceedings.